Kinerja Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Bintan dalam Fungsi Legislasi Tahun 2018 - Neng Suryanti Nengsih; Junriana, Junriana; nur azizah; DIDYL CHOIROEL (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
The performance of the legislative body in the political system is a reflection of the level of implementation of democratic state life, so that the study of the factors that influence the performance of this institution becomes something important, considering the main tasks and functions carried out by regional legislative institutions in the current era of autonomy. To carry out these functions, the Regional People's Representative Council of Bintan Regency is equipped with duties, powers, obligations and rights. One of the functions of the House of Representatives which is very important in order to support the implementation of broad autonomy in the Region is the function of Legislation. To carry out the Legislative function of the House The Regional Representatives of Bintan Regency are given various rights, one of which is the right to submit a draft regional regulation and the right to amend the Raperda; or the implementation of the Legislative Function must be followed up with a Regional Regulation (Perda). The legislative function is based on the initiative of DPRD members in forming regional regulations. Bintan Regency DPRD Performance in the 2017-2018 Legislation Function. In this case, there have been several community aspirations submitted to the Bintan Regency DPRD which have been followed up by the DPRD and the Regional Government by establishing a Regional Regulation. The function of the Bintan Regency DPRD as a facilitator that is able to bridge differences in interests between fellow community groups or between these groups and the Regional Government has been fulfilled. The performance that you want to know through the economic marketplaze approace approach is related to the level of production produced in this case, the performance of DPRD members as seen from the number of Regional Government Drafts proposed with the results of Regional Regulations which are realized through the formation of regional regulations for Bintan Regency. And it can be seen from the results of the regional regulations that were passed whether it was in accordance with the situation in the Bintan Regency area.